Raz jeszcze o sondażowych szacunkach zasięgu wydawnictw podziemnych lat osiemdziesiątych - Mielczarek, Adam (Pamięć i Sprawiedliwość, 2014)
The purpose of this article is to present data concerning readership of independent publications in the period after the introduction of martial law. The author mainly analyses survey-based data collected ex post, including the results of recent studies which have not been published yet. The data collected documents significant differences in the access to underground publications in various sizes of centres, in groups of various educational background and in environments declaring different opposition behaviour. It is a good indicator of the range of influence of the opposition of the time.